Análise da expressão gênica em Schistosoma mansoni induzida pelo pareamento sexual epelo sexo do hospedeiro através da técnica dos microarranjos de DNA - Michael Waisberg (2007)
The parasitic trematode Schistosoma mansoni is one of the major causative agents ofSchistosomiasis, a disease that affects approximately 200 million people, mostly indeveloping countries. Since much of the pathology is associated with eggs laid by thefemale worm, understanding the mechanisms involved in oogenesis and sexualmaturation is an important step towards the discovery of new targets for effective drugtherapy. In order to study gene transcripts associated with sexual maturation, ovipositionand host sex effect we compared the gene expression profiles of sexually mature andimmature parasites from both male and female mice using DNA microarrays. Our resultsshow that 265 transcripts are differentially expressed in adult females and 53 in adultmales when mature and immature worms from female mice are compared. Of the genesdifferentially expressed, 55% are expressed at higher levels in paired females while theremaining 45% are more expressed in unpaired ones, and 56.6% are expressed at higherlevels in paired male worms while the remaining 43.4% are more expressed in immatureparasites. The results also show that host sex causes differential expression of 11 genes infemale parasites and of 134 in male parasites. Of the differentially expressed genes infemale worms related to host sex, 10 were more expressed in female worms from malemice, while of the 134 differentially expressed genes in male parasites, 79 (59%) weremore expressed in worms from female mice suggesting that the communication betweenhosts and parasites is more frequent when they are from opposite sexes. A myriad of newhost sex and maturation associated transcripts were identified, therefore enabling theacquisition of a large body of knowledge about the communication between parasites ofopposite sexes, as well as the communication between host hormones and schistosomes.